2022
DOI: 10.3390/jpm12030331
|View full text |Cite
|
Sign up to set email alerts
|

Biased β-Agonists Favoring Gs over β-Arrestin for Individualized Treatment of Obstructive Lung Disease

Abstract: Signals from G-protein-coupled receptors (GPCRs) are the most frequently targeted pathways of currently prescribed therapeutics. Rather than being a simple switch, it is now evident that a given receptor can directly initiate multiple signals, and biasing to achieve signal selectivity based on agonist structure is possible. Biased agonists could direct therapeutically favorable pathways while avoiding counterproductive or adverse reaction pathways. For obstructive lung diseases, β2-adrenergic receptor (β2AR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…After GPCR is stimulated by extracellular signals, activated GPCR can induce structural rearrangement of its cytoplasmic region ( 199 ) and induce intracellular signal transduction through classical G protein or GRK-arrestin pathway ( Figure 2 ) ( 200 , 201 ), and this signal transduction can be biased in three ways. System bias refers to the differential expression of signaling pathways of the same receptor or ligand in a different time, space, and cell type.…”
Section: The Bias Of Gpcr Expression: G Protein or Grk-arrestin Pathwaymentioning
confidence: 99%
“…After GPCR is stimulated by extracellular signals, activated GPCR can induce structural rearrangement of its cytoplasmic region ( 199 ) and induce intracellular signal transduction through classical G protein or GRK-arrestin pathway ( Figure 2 ) ( 200 , 201 ), and this signal transduction can be biased in three ways. System bias refers to the differential expression of signaling pathways of the same receptor or ligand in a different time, space, and cell type.…”
Section: The Bias Of Gpcr Expression: G Protein or Grk-arrestin Pathwaymentioning
confidence: 99%
“…What also supports this therapeutic idea is that balanced β 2 -AR agonists run the risk of therapeutic tolerance or loss of response with prolonged treatment, as data suggests that desensitization and downregulation of β 2 -ARs occurs downstream of β-Arr binding (Gagnon et al, 1998). Moreover, these drugs have been the subject of much scrutiny due to the increased risk of asthma morbidity/mortality associated with their chronic usage (Kim et al, 2021;Tokmakova et al, 2022). More recently, it was shown that adrenaline-dependent β 2 -AR signaling activation is required for the development of the asthma phenotype in an allergen-driven (Ova S/C) murine asthma model, and chronic treatment with various β-blockers has yielded conflicting results, likely due to drug-specific biased signaling (Thanawala et al, 2013;Thanawala et al, 2015) Recent evidence demonstrates critical roles for post-translational modifications other than phosphorylation in intracellular signaling.…”
Section: β Adrenoceptorsmentioning
confidence: 96%
“…One can easily find reports that compare the effects of different types of β2AR agonists (mainly short acting vs long acting) on the bronchia [ 82 , 83 ], but comparative studies that focus on the effects of the different agonists in lung inflammation are lacking, mainly the ones focused on immunological and molecular mechanisms. Still, the notion that biased agonists (agonist that preferentially triggers a downstream molecular pathway; i.e., carvedilol, a β2AR agonist that preferentially triggers β-arrestin signaling instead of cAMP-dependent signaling after [ 84 ]) can produce different clinical outcomes is starting to get more attention in different disease models [ 85 , 86 ]. There are interesting research paths to be pursued in this issue.…”
Section: Concluding Remarks: Do We Really Understa...mentioning
confidence: 99%